Application of Intravoxel Incoherent Motion Diffusion-Weighted Imaging in Predicting and Monitoring Early Efficacy of Anti-Angiogenic Therapy in the C6 Glioma Rat Model - Hou, Weishu; Xue, Yangyang; Qian, Yinfeng; Pan, Hongli; Xu, Man; Shen, Yujun; Li, Xiaohu; Yu, Yongqiang (Frontiers in Oncology, 2022)
Objective To investigate the feasibility of intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) in evaluating early effects of anti-angiogenic therapy in the C6 glioma rat model. Methods Twenty-six rats of C6 glioma model were randomly divided into a treatment group (received bevacizumab) and a ontrol group (physiological saline). IVIM-DWI was performed on days 0, 1, 3, 5, and 7 after anti-angiogenic therapy and tumor growth and IVIM-DWI parameters were dynamically observed. Hematoxylin and eosin, CD34 microvessel density (MVD), proliferation of cell nuclear antigen (PCNA), and Hif-α staining was performed on day 7. One-way ANOVA was used to compare intra-group differences and an independent-samples t-test was used to compare inter-group differences of MRI parameters. Correlations between IVIM-DWI parameters, tumor size and pathological results were analyzed. Results The relative change in tumor volume (ΔVolume) in the two groups differed significantly on days 5 and 7 (P = 0.038 and P < 0.001). The perfusion-related parameters D* and f-values decreased in the treatment group and demonstrated significant differences compared with the control group on days 3, 5 and 7 (P = 0.033, P < 0.001 and P < 0.001, respectively). The diffusion-related parameters ADC and D-values increased in the treatment group and were found to be significantly differently different from the control group on days 5 and 7 (both P < 0.001). The initial D-value showed a negative correlation with ΔVolume (γ = -0.744, P < 0.001), whereas the initial D*-value and relative change of D-value had a positive correlation with ΔVolume (γ = 0 .718, P < 0.001 and γ = 0.800, P < 0.001, respectively). MVD was strongly positively correlated with D*-value (r = 0.886, P = 0.019), PCNA was negatively correlated with ADC and D-values (r = -0.848, P = 0.033; and r = -0.928 P = 0.008, respectively) and Hif-1α was strongly negatively correlated with D*-value (r = -0.879, P = 0.010). Conclusion IVIM-DWI was sensitive and accurate in predicting and monitoring the effects of early anti-angiogenesis therapy in a C6 glioma rat model.